2007
DOI: 10.1523/jneurosci.2099-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Kisspeptin Receptor GPR54 Is Required for Sexual Differentiation of the Brain and Behavior

Abstract: GPR54 is a G-protein-coupled receptor, which binds kisspeptins and is widely expressed throughout the brain. Kisspeptin-GPR54 signaling has been implicated in the regulation of pubertal and adulthood gonadotropin-releasing hormone (GnRH) secretion, and mutations or deletions of GPR54 cause hypogonadotropic hypogonadism in humans and mice. Other reproductive roles for kisspeptin-GPR54 signaling, including the regulation of developmental GnRH secretion or sexual behavior in adults, have not yet been explored. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(186 citation statements)
references
References 53 publications
12
171
0
3
Order By: Relevance
“…In contrast, we also show that the blockade of NO synthesis blunts the LH surge in steroid-primed mice, known to involve the activation of kisspeptin-GPR54 signaling (Clarkson et al, 2008) initiated by the kisspeptin neuronal population residing in the anteroventral periventricular nucleus (Clarkson et al, 2008;Gottsch et al, 2009;Mayer et al, 2010). Together, these results suggest that NO-and kisspeptin-synthesizing neurons interact in synergy to coordinate the progression of the ovarian cycle, and thus reconcile the recent evidence that kisspeptin signaling plays a key role in the neuroendocrine control of reproduction (Funes et al, 2003;Seminara et al, 2003;d'Anglemont de Tassigny et al, 2007b;Dungan et al, 2007;Kauffman et al, 2007;Lapatto et al, 2007;Clarkson et al, 2008;Mayer et al, 2010;Mayer and Boehm, 2011), with the originally postulated role for NO in controlling GnRH secretion (Rettori et al, 1993;Mahachoklertwattana et al, 1994), the onset of the preovulatory GnRH/LH surge (Bonavera et al, 1993;Aguan et al, 1996;d'Anglemont de Tassigny et al, 2007a), and fertility (Gyurko et al, 2002). These findings also raise the exciting possibility that the estrogen-evoked kisspeptin-mediated activation of nNOS neurons in proestrus serves as an intermediate synchronizing switch for the GnRH system that enables the transition between pulsatile and peak release of GnRH (Christian and Moenter, 2010).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In contrast, we also show that the blockade of NO synthesis blunts the LH surge in steroid-primed mice, known to involve the activation of kisspeptin-GPR54 signaling (Clarkson et al, 2008) initiated by the kisspeptin neuronal population residing in the anteroventral periventricular nucleus (Clarkson et al, 2008;Gottsch et al, 2009;Mayer et al, 2010). Together, these results suggest that NO-and kisspeptin-synthesizing neurons interact in synergy to coordinate the progression of the ovarian cycle, and thus reconcile the recent evidence that kisspeptin signaling plays a key role in the neuroendocrine control of reproduction (Funes et al, 2003;Seminara et al, 2003;d'Anglemont de Tassigny et al, 2007b;Dungan et al, 2007;Kauffman et al, 2007;Lapatto et al, 2007;Clarkson et al, 2008;Mayer et al, 2010;Mayer and Boehm, 2011), with the originally postulated role for NO in controlling GnRH secretion (Rettori et al, 1993;Mahachoklertwattana et al, 1994), the onset of the preovulatory GnRH/LH surge (Bonavera et al, 1993;Aguan et al, 1996;d'Anglemont de Tassigny et al, 2007a), and fertility (Gyurko et al, 2002). These findings also raise the exciting possibility that the estrogen-evoked kisspeptin-mediated activation of nNOS neurons in proestrus serves as an intermediate synchronizing switch for the GnRH system that enables the transition between pulsatile and peak release of GnRH (Christian and Moenter, 2010).…”
Section: Discussionsupporting
confidence: 62%
“…Kisspeptin-expressing neurons, which are found primarily in the hypothalamus, directly innervate and stimulate the electrical activity of GnRH neurons, which express the kisspeptin receptor GPR54 ). Mice with a targeted deletion of Gpr54 are sterile (Funes et al, 2003;Seminara et al, 2003;Dungan et al, 2007;Kauffman et al, 2007;Lapatto et al, 2007), and kisspeptin-GPR54 signaling appears essential for the GnRH neuronal activation that initiates ovulation (Clarkson et al, 2008). In addition to acting directly on GnRH neurons, an increasing body of evidence suggests that kisspeptin also operates on unidentified neurons to modulate the strength of synaptic afferents and regulate GnRH secretion (Pielecka-Fortuna et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…From a physiological perspective, the prolonged effects of kisspeptin in GnRH neurons are probably important for sexual maturation and adult reproduction (Han et al, 2005;Kauffman et al, 2007a). It is generally believed that kisspeptins are the endogenous ligands for the GPR54 receptor (Kotani et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a male-biased sex difference in the percentage of GnRH neurons expressing GPR54 is present on the day of birth in mice [74]. In addition, studies by Kauffman et al [75] using a global GPR54 knockout mouse demonstrated that the GPR54 is necessary for normal sexual differentiation of the male brain and behaviour. Male mice lacking the kisspeptin receptor had a greater number of THimmunoreactive, and Kiss1 mRNA expressing cells in the RP3V than wild-type littermates, and had a feminized number of neurons in the spinal nucleus of the bulbocavernosus.…”
Section: Kisspeptin Neurons As Orchestrators Of the Neonatal Testostementioning
confidence: 99%